1982
DOI: 10.1111/j.0954-6820.1982.tb03206.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Metamucil on Postprandial Blood Glucose and Plasma Gastric Inhibitory Peptide in Insulin‐dependent Diabetics

Abstract: ABSTRACT. Postprandial hyperglycemia was significantly (p<0.05) reduced during administration of the fibre supplement Metamucil in nine insulin‐dependent diabetics. A similar but less pronounced effect was also found on the plasma gastric inhibitory polypeptide secretion. Six subjects noted an increased frequency of hypoglycemic episodes, and reductions in insulin dosage might have been necessary if the experiment had continued longer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(2 citation statements)
references
References 15 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…However, these effects are predominantly observed in type II diabetics and with chronic consumption of psyllium. Other studies show variable effects of psyllium on blood glucose responses in normal and diabetic subjects ( 38 41 ) . The inconsistent results may be attributed to how psyllium is administrated and partly to the physical properties of the psyllium.…”
Section: Discussionmentioning
confidence: 95%
“…However, these effects are predominantly observed in type II diabetics and with chronic consumption of psyllium. Other studies show variable effects of psyllium on blood glucose responses in normal and diabetic subjects ( 38 41 ) . The inconsistent results may be attributed to how psyllium is administrated and partly to the physical properties of the psyllium.…”
Section: Discussionmentioning
confidence: 95%
“…SDF significantly decreased the postprandial plasma glucose in DM patients after 2 hours (mean reduction 14.2±5.2 vs 10.6±3.1 mmol/L). 7 In earlier research, it was found that psyllium decreased either the postprandial blood glucose concentrations 16 or the fasting plasma glucose level 8 in people with type 2 diabetes. In a different study, psyllium only had an effect on diabetic subjects' glycemic reaction to a test meal of flaked bran cereal when it was mixed into or sprinkled on top of the cereal.…”
Section: Discussionmentioning
confidence: 97%